2021
DOI: 10.1055/a-1470-0446
|View full text |Cite
|
Sign up to set email alerts
|

13C NMR Dereplication Using MixONat Software: A Practical Guide to Decipher Natural Products Mixtures

Abstract: The growing use of herbal medicines worldwide requires ensuring their quality, safety, and efficiency to consumers and patients. Quality controls of vegetal extracts are usually undertaken according to pharmacopeial monographs. Analyses may range from simple chemical experiments to more sophisticated but more accurate methods. Nowadays, metabolomic analyses allow a fast characterization of complex mixtures. In the field, besides mass spectrometry (MS), nuclear magnetic resonance spectroscopy (NMR) has gained i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…From such DBs containing NPs together with their δ C‐SDF values, the CTypeGen routine included in MixONat created a suitable DB: It read the spatial data file (SDF) and sorted chemical shifts by carbon type. The required c‐type SDF was then created, i.e., c‐type Propolis DB1 43,44 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From such DBs containing NPs together with their δ C‐SDF values, the CTypeGen routine included in MixONat created a suitable DB: It read the spatial data file (SDF) and sorted chemical shifts by carbon type. The required c‐type SDF was then created, i.e., c‐type Propolis DB1 43,44 …”
Section: Methodsmentioning
confidence: 99%
“…Thus, the aim of this study was to characterize major compounds from propolis samples collected in various phytogeographical zones of Benin and Congo (Africa) using 13 C nuclear magnetic resonance (NMR) dereplication with MixONat software 43,44 . A preliminary study using a database (DB) containing NPs previously reported from propolis together with their 13 C predicted chemical shifts ( δ C ) did not yield any usable data compared to the satisfactory results usually obtained with plant extracts 43–45 .…”
Section: Introductionmentioning
confidence: 95%
“…The database (DB) of natural products (NPs) (CH-NMR-NP DB), containing the experimental 1 H (δH) and 13 C (δC) chemical shifts of 32854 NPs, was prepared as previously described, from the data available on the dedicated JEOL RESONANCE Inc. website (Bruguière et al 2020), available at https://www.j-resonance.com/en/nmrdb/. Additionally, DBs containing the predicted δC values of NPs isolated from species belonging to the Clusia (ClDB) and Calophyllum (CaDB) genera were prepared by including the 166 and 307 metabolites described from Clusia and Calophyllum genera, respectively, in the SciFinder ® website (Bruguière et al 2021). The C-typeGen program included in the MixONat software created then a DB, in the format required by MixONat (Bruguière et al 2020), containing the predicted δC values for the methyl, methylene, methine, and quaternary carbons of each metabolite.…”
Section: Databases Of Natural Products For Dereplicationmentioning
confidence: 99%
“…Despite its indubitable assets, UPLC-HRMS may nevertheless encounter certain limitations linked to solvent limitation, ionizability of analytes and the differentiation of (stereo)isomers. Addressing these issues, matrix free laser desorption ionization-HRMS (LDI-HRMS) 3 assisted by 13C NMR dereplication (MixONat) 4 may provide alternative methodological approaches. As a working example, a holistic chemometric approach was applied using UPLC-qTOF versus LDI-HRMS assisted by 13C NMR for the identification of anti-AGEs NPs (ability to prevent the formation of advanced glycation end products 5 ) from Garcinia parvifolia bark extracts.…”
mentioning
confidence: 99%